“Weaving a body out of words”: Playwriting strategies for trans-informed research-based theatre - Cook, Christina (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2025)
This article addresses the question: What are the expansive possibilities offered by a trans-informed Research-based Theatre (RbT) creation framework? Drawing on excerpts from an autoethnographic playscript which centres on my experiences as a graduate student while coming out as a nonbinary trans woman, I explore specific and adaptable strategies for trans-informed RbT playwriting. Playwriting is an essential component of the RbT creation process, and the strategies explored in this article may inform RbT practitioners’ approach in the classroom and beyond.